Cytosolic p120-catenin regulates growth of metastatic lobular carcinoma through Rock1-mediated anoikis resistance - Ron C.J. Schackmann; Miranda van Amersfoort; Judith H.I. Haarhuis; Eva J. Vlug; Vincentius A. Halim; Jeanine M.L. Roodhart; Joost S. Vermaat; Emile E. Voest; Petra van der Groep; Paul J. van Diest; Jos Jonkers; Patrick W.B. Derksen (The Journal of Clinical Investigation, 2011)
Metastatic breast cancer is the major cause of cancer-related death among women in the Western world. Invasive carcinoma cells are able to counteract apoptotic signals in the absence of anchorage, enabling cell survival during invasion and dissemination. Although loss of E-cadherin is a cardinal event in the development and progression of invasive lobular carcinoma (ILC), little is known about the underlying mechanisms that govern these processes. Using a mouse model of human ILC, we show here that cytosolic p120-catenin (p120) regulates tumor growth upon loss of E-cadherin through the induction of anoikis resistance. p120 conferred anchorage independence by indirect activation of Rho/Rock signaling through interaction and inhibition of myosin phosphatase Rho–interacting protein (Mrip), an antagonist of Rho/Rock function. Consistent with these data, primary human ILC samples expressed hallmarks of active Rock signaling, and Rock controlled the anoikis resistance of human ILC cells. Thus, we have linked loss of E-cadherin — an initiating event in ILC development — to Rho/Rock-mediated control of anchorage-independent survival. Because activation of Rho and Rock are strongly linked to cancer progression and are susceptible to pharmacological inhibition, these insights may have clinical implications for the development of tailor-made intervention strategies to better treat invasive and metastatic lobular breast cancer.